2021
DOI: 10.1016/j.celrep.2021.109489
|View full text |Cite
|
Sign up to set email alerts
|

Antibody interference by a non-neutralizing antibody abrogates humoral protection against Plasmodium yoelii liver stage

Abstract: Highlights d We isolate a non-neutralizing antibody from PyCSPimmunized BALB/cJ mice d A non-neutralizing Ab, RAM1, abrogates the blocking capacity of an aCSP NAb d A non-neutralizing Ab, RAM1, reduces the vaccine efficacy in mice in vivo d Further exploration for the role of pre-existing nNAbs in the field is warranted

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…2C). The known inhibitory anti-PyCSP mAb 2F6 38,39 reduced both inhibition and traversal in this assay, as expected (Fig. 2B and C).…”
Section: Pytrap Polyclonal Antibodies Can Prevent Parasite Infection ...supporting
confidence: 87%
See 1 more Smart Citation
“…2C). The known inhibitory anti-PyCSP mAb 2F6 38,39 reduced both inhibition and traversal in this assay, as expected (Fig. 2B and C).…”
Section: Pytrap Polyclonal Antibodies Can Prevent Parasite Infection ...supporting
confidence: 87%
“…Studies examining CSP-elicited antibody responses have shown that within a polyclonal antibody population only a subset are highly potent antibody clones, and their distinguishing binding properties can be quite nuanced 39,44,45,[54][55][56][57][58] . Understanding the characteristics associated with protection is crucial for the development of superior mAb products and vaccine immunogens, yet such studies have not been previously performed for TRAP or other non-CSP pre-erythrocytic antibody targets.…”
Section: Discussionmentioning
confidence: 99%
“…We may therefore need to optimize cadence and epitope context for presenting these two short epitopes in tandem 70 . At the parasite level, Vijayan et al 71 have shown possible interference when monoclonal antibodies to the major and minor repeats of P. yoelii CSP are bound simultaneously; likewise, there is no evidence that P. falciparum mAb 317 and CIS43 can synergize in vitro (unpublished data). Therefore, immune-broadening using multiple short inhibitory epitopes on a single vaccine construct was complex and, in this instance, was found detrimental to vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The repeat region in Py CSP contains two general motifs that make up the longer, N -terminal major repeat region and the shorter, more C-terminal minor repeats ( Fig 2B ). The minor repeat region is the target of potent α- Py CSP neutralizing activity of mAb 2F6 [ 29 31 ] but neutralization by mAbs targeting the major repeat region has not been reported. At week 3, the strains had equivalent IgG titers to the major repeat peptide, but BALB/cJ mice had significantly higher titers to the minor repeat peptide ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this possibility, we investigated whether the major repeat also could be a target for NAbs, or whether neutralization is solely mediated through the minor repeat motif as observed for mAb 2F6. We previously characterized a non-neutralizing antibody (nNAb), RAM1, which binds to the major repeat with relatively low affinity, does not induce the CSP reaction, nor protects in vitro or in vivo [ 31 ]. In this study, we isolated a mAb RAM2, which also binds to an epitope in the major repeat motif like RAM1 (Figs 3A and S4A ).…”
Section: Resultsmentioning
confidence: 99%